How employee assistance programs (EAP) influence employee stress levels through quality of work life - Melandari, Defi; Jannah S, Miftahul (Junal Ilmu Manajemen, 2025)
This study aims to analyze the relationship between Employee Assistance Program (EAP), Quality of Work Life (QWL), and employee work stress levels at PT. Delta Artha Bahari Nusantara. The study used a quantitative approach with a survey method of 108 permanent and contract employees. The variables analyzed include EAP as an independent variable, QWL as a mediating variable, and work stress levels as a dependent variable. Data were analyzed using Structural Equation Modeling (SEM) to test the relationship between variables. The results showed that EAP had a significant positive effect on QWL with a t value = 10.033 (p <0.05), but did not have a significant direct effect on work stress with a t value = 0.208 with p = 0.835 (p>0.05). Conversely, QWL had a significant effect in reducing work stress levels with t = 12.993 (p <0.05). In addition, QWL significantly mediated the effect of EAP on work stress with t = 7.128 (p < 0.05). Descriptive analysis showed that very high work stress was still found even though EAP was frequently implemented, highlighting the need to improve the effectiveness of the program. It can be concluded that improving QWL plays an important role in reducing work stress, while EAP significantly contributes to improving QWL. Therefore, companies need to integrate the implementation of EAP with QWL improvement strategies to create a healthier, more productive, and more supportive work environment for employee well-being.